Cheating, corruption, and concealment the roots of dishonesty - Prooijen, Jan-Willem van 1975-; Lange, Paul A. M. van (Cambridge, [England] Cambridge University Press, 2016)
"Dishonesty is ubiquitous in our world. The news is frequently filled with high-profile cases of corporate fraud, large-scale corruption, lying politicians, and the hypocrisy of public figures. On a smaller scale, ordinary people often cheat, lie, misreport their taxes, and mislead others in their daily life. Despite such prevalence of cheating, corruption, and concealment, people typically consider themselves to be honest, and often believe themselves to be more moral than most others. This book aims to resolve this paradox by addressing the question of why people are dishonest all too often. What motivates dishonesty, and how are people able to perceive themselves as moral despite their dishonest behaviour? What personality and interpersonal factors make dishonesty more likely? And what can be done to recognize and reduce dishonesty? This is a fascinating overview of state-of-the-art research on dishonesty, with prominent scholars offering their views to clarify the roots of dishonesty"-- Provided by publisher.
"People can be dishonest creatures. Many exaggerate their achievements, downplay their moral failures, lie about the number of hours they have put into a collaborative project, and cheat on their spouses. When reporting income taxes, many people are tempted to strategically "forget" sources of income. Treasurers of professional organizations are found to transfer collective funds to their private account. Also prominent people in society are regularly caught performing dishonest behavior. The past decade has seen various instances of high-profile corporate fraud cases, in which powerful managers embezzled large sums of money, or deliberately misrepresented their profits to stakeholders. Politicians that publicly stand up for traditional family values have been discovered in shady hotel rooms with prostitutes. Prolific scientists have committed plagiarism or data fraud. In fact, at the moment of writing this chapter, the FIFA corruption scandal is still unfolding, and many high-ranked officials have been arrested under the charge of accepting bribes when allocating important soccer tournaments to competing countries. Clearly, dishonesty is part of human nature, and can be found in all layers of society"-- Provided by publisher.
Table of contents: 1. Cheating, corruption, and concealment: an introduction to dishonesty Jan-Willem van Prooijen and Paul A. M. van Lange; Part I. Motivations for Dishonesty: 2. Moral motivation: a closer look C. Daniel Batson; 3. Beyond 'being good frees us to be bad': moral self-licensing and the fabrication of moral credentials Daniel A. Effron; 4. Deception as a means to an end: an instrumental approach Wolfgang Steinel, Lukas Koning, Eric van Dijk and Ilja van Beest; Part II. Justifying Dishonesty: 5. How moral flexibility constrains our moral compass Francesca Gino; 6. Always the hero to ourselves: the role of self-deception in unethical behaviour Celia Moore; 7. Not for my sake: preventing others from using potential beneficiaries' benefits as justifications for dishonesty Scott S. Wiltermuth and Medha Raj; 8. Corrupt collaboration: a behavioral ethics approach Shaul Shalvi, Ori Weisel, Sys Kochavi-Gamliel and Margarita Leib; Part III. Influences on Dishonesty: 9. Narcissism and dishonesty: the SAC model W. Keith Campbell and Lane Siedor; 10. When being creative frees us to be bad: linking creativity with moral licensing Lynne C. Vincent and Evan Polman; 11. Wealth and wrongdoing: social class differences in ethical reasoning and behavior Paul K. Piff, Daniel M. Stancato and E. J. Horberg; 12. Power, dishonesty, and justice Steven L. Blader and Andy J. Yap; Part IV. Reducing Dishonesty: 13. Religion, deception, and self-deception Stephanie R. Kramer and Azim F. Shariff; 14. The ergonomics of ethics Andy J. Yap; 15. When opposition is beneficial: the case of productive disobedience Piero Bocchiaro; 16. A cognitive approach to elicit verbal and nonverbal cues to deceit Aldert Vrij, Ronald P. Fisher, Hartmut Blank, Sharon Leal and Samantha Mann.
Includes bibliographical references and index.
Keywords: Ethics -- Psychological aspects; Honesty; Corruption; Deception